PENGARUH JUMLAH SIMPANAN DAN JUMLAH PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA PADA KOPERASI KREDIT HANDAYANI BAJAWA - Yorni Mbulu; Pius Bumi Kellen; Leony Magdalena Ndoen; Bei Marselinus (Universitas Nusa Cendana, 2019)
This study entitled '' The Influence of Total Deposits And Total Member Loans To The Residual Return On Credit Cooperation Handayani Bajawa '' increase in the remaining results of operations depends on the aspect of the volume of business runs sufficient cooperative namely the availability of sufficient capital either from savings or loan members. To achieve all that, it must be supported by the participation of members. The purpose of this study is to determine the effect of the amount of stock saving, the amount of loan members to the rest of the business results on Credit Handayani Bajawa cooperative. Data collection technique is done by studying report- lapora Annual Members Meeting (RAT). The analysis method used is model test, multiple linear analysis, multi ple correlation analysis, simultaneous test, partial test. The results show that there is a very strong relationship between the amount of saha deposit, the amount of loan to the rest of the business result. Thus, in order to increase the rest of the business results, the handyman Credit Koperasi Handayani Bajawa need to pay attention to these two variables namely the amount of stock saving and lending amount.